2001
DOI: 10.1161/hs1201.099383
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual and Reproductive Factors for Subarachnoid Hemorrhage Risk in Women

Abstract: Background and Purpose-We sought to examine the relationship between menstrual and reproductive factors and the risk of subarachnoid hemorrhage (SAH), using a case-control study. Methods-Cases consisted of a consecutive series of 124 women patients with first spontaneous SAH aged 30 to 79 years and confirmed aneurysm(s) by angiography and/or CT scan. Hospital and community controls subjects were identified, matched to each case by age (Ϯ2 years). Results-Increased SAH risk was associated with (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 32 publications
2
42
1
Order By: Relevance
“…13 Studies have suggested that the gender difference is related to hormonal status, with premenopausal women, 32 those of older age at the birth of their first child, and those of older age at the onset of menarche at reduced risk for SAH. 33 There appear to be racial differences in risk of SAH. Black Americans are at higher risk than white Americans.…”
Section: Incidence and Prevalence Of Aneurysmal Sahmentioning
confidence: 99%
“…13 Studies have suggested that the gender difference is related to hormonal status, with premenopausal women, 32 those of older age at the birth of their first child, and those of older age at the onset of menarche at reduced risk for SAH. 33 There appear to be racial differences in risk of SAH. Black Americans are at higher risk than white Americans.…”
Section: Incidence and Prevalence Of Aneurysmal Sahmentioning
confidence: 99%
“…Most longitudinal studies were initiated in the 1970s and were restricted to the US, Japanese, UK, Korean, and Finnish populations. Of the 23 case-control studies, 10 (63% of SAH cases) [12][13][14][15][16][17][18][19][20][21] were population based and 13 hospital based, [22][23][24][25][26][27][28][29][30][31][32][33][34] covering a variety of populations: American (United States), Latin American (Chile, Colombia, Mexico, Brazil, and Jamaica), European (Norway, Germany, Hungary, Portugal, Denmark, Yugoslavia, Slovenia, Finland, and the United Kingdom), African (Kenya, Zambia, and Zimbabwe), and Australasian (China, Indonesia, Thailand, Australia, New Zealand, and Japan). Overall, 3936 cases of SAH (892 cases in longitudinal studies [9 223 763 person-years of follow-up] and 3044 cases in case-control studies) were available for the analysis, thus allowing 1984 more cases of SAH to be analyzed than in the previous overview.…”
Section: Resultsmentioning
confidence: 99%
“…Our methods were described previously in detail (Okamoto et al, 2001(Okamoto et al, , 2003Okamoto and Horisawa, 2006). Briefly, we recruited all consecutive and incident SAH patients admitted at two large medical hospitals located in Nagoya from April 1992 to March 1997.…”
Section: Methodsmentioning
confidence: 99%